Quantitative assessment of early liver fibrosis in rats using 13N-NH3·H2O PET/CT. Issue 1 (January 2016) - Han, Ting-Ting; Du, Ming; Zhang, Xin; Cao, Li; Li, Hong; Zhao, Zhou-She; Guo, Qi-Yong; Xin, Jun
Abstract : Objective: To investigate the value of 13 N-NH3 ·H2 O PET/computed tomography (CT) and the inhibitor, acetazolamide (ACZ), in the quantitative diagnosis of early liver fibrosis and the assessment of liver fibrosis stage. Materials and methods: Twenty-four male Wistar rats (293.54±37.99 g) were used in this study and grouped by pathology after biopsy. Using 13 N-NH3 ·H2 O as an imaging agent and ACZ as an aquaporin 1 inhibitor, the rats were subjected to a dynamic PET/CT scan for 45 min. According to data reconstruction and imaging analysis, we calculated the mean standard uptake value (SUVmean ) of the liver at the time points of 20, 90 s, 5, 10, 15, 20, and 25 min. From the results of 13 N-NH3 ·H2 O, the liver SUVmean in the control group and the liver fibrosis model group at different time points were compared. In addition, blood perfusion, interstitial diffusion, and 13 N-NH3 ·H2 O metabolism of the two groups were compared. Single-factor analysis of variance was used to analyze the differences between the SUVs in the groups at any time point and the paired-sample t -test was used to compare the SUVs before and after addition of the inhibitor. Results: We included four rats in the control group (S0) and 20 rats in the liver fibrosis group (which included early-stage S1: 11 rats, progressive-stage S2+S3+S4: nine rats). Three rats in S0, seven rats in S1, and six rats in S2+S3+S4 were paired. The SUVmean at 90 s was statistically different ( P <0.05); however, the other groups showed statistical difference at all time points ( P >0.05). After the addition of the inhibitor, ACZ, the SUVmean of S0 and S2+S3+S4 at 10, 15, 20, and 25 min was statistically different ( P <0.05). Conclusion: 13 N-NH3 ·H2 O PET/CT may aid the diagnosis of liver fibrosis. 13 N-NH3 ·H2 O PET/CT combined with ACZ may help distinguish between the early stage and the progressive stage of liver fibrosis.